An Analysis Of Sentence Structure In The Students Writing: A Case Study At Third Class Of SMA Al-Ikhwan Kota Bima - Rahman, Abdur; Feriyadin, Feriyadin (STKIP Harapan Bima, 2022)
The title of the research is An Analysis of Sentence Structure in the Student Writing. This study is aimed at finding out errors of sentence or to know the factor that caused the students have problem in writing. The population of this study was SMA AL-Ikhwan Kota Bima that is school have 1 (one) class for third class, the number of students of that class is consists of 30 (thirty) students as sampling. The method used in this study was descriptive. The method of collecting data was the students write their experience or their story. The method of analyzing data used in this study was tabulate of errors, classify the errors, and identify the errors. In study found kinds of error such as interference, omission, addition, substitution, and ordering. The conclusion of this study was that there are 14 (fourteen) students get poor, 14 (fourteen) students get satisfaction, and 2 students get excellent, and the accumulation of errors found 4.43 or 41% the average of incorrect sentences and 7 or 58% of correct sentences from average of 11 (eleven) sentences in expository writing skill made by 30 (thirty) students. The suggestion in this study was for the students should be learning more seriously, to overcome the errors the students should do self-correction for their errors or mistake in writing skill, the students have to get more motivation, study hard, and practice always every time or every day, and the students should each other to correct their friends errors in writing skill. For the English teachers should not ignore the teaching of tenses, grammar or sentence structures. Because it is very important to be learnt without grammar or structure it is impossible to writing well, the English teachers should give better chances for their students to find out and to overcome the errors they commit, the English teacher should more emphasize on teaching programs by using the effective methods, and the English teachers should active and control the students lazy to study in English lesson